Application of georadar (GPR) for the characterization of floor thrust in the region of Serra da Matriculada, municipality of Datas (MG) (Research, Society and Development, 2020)
Georadar (GPR) corresponds to a geophysical method that, among other applications, has been used in the mapping of subsurface geological features. Thus, this technique was used for the structural characterization of lithotypes in Serra da Matriculada, Datas (MG). Two profiles with E-W direction and one with N-S direction were performed, perpendicular to the shear zones responsible for stratigraphic inversions. Among the characteristics observed in radargrams, two patterns of continuous reflection stand out: (1) inclination towards the east quadrants, consistent with the foliation planes of the outcropping lithotypes and (2) oblique to the first reflectors, correlated to the family of fractures with direction NS and dive to the west quadrants. The profile with N-S direction indicates a normal fault, responsible for the absence of correlated lithotypes to Barão do Guaicuí Formation and Gouveia Complex in the southern portion of the area. The limitations associated with the use of GPR are the presence of lithotypes with conductive electrical characteristics and, locally, of electromagnetic noise.